Acral Purpura Fulminans With Erythrocyte-Associated Streptococcus pneumoniae: A Case Report - Donald L. Granger; Jeannine Pembroke; Todd R. Gordon (Annals of Internal Medicine: Clinical Cases)
A patient presented with acral purpura fulminans caused by Streptococcus pneumoniae septicemia. With antibiotics and intensive care, he survived but required amputations of both hands and feet due to ischemic necrosis. We observed diplococci adherent to erythrocytes on blood smear. This previously described phenomenon, named immune adherence, requires complement. Opsonized pneumococci bind to complement receptors on human erythrocytes. Circulating immune adherent pneumococci are delivered by erythrocytes to fixed splenic macrophages for bacterial killing. We hypothesize that defective reticuloendothelial function most likely contributed to our patient's overwhelming infection with septic syndrome, disseminated intravascular coagulation, and acral purpura fulminans.